Avaliação da potencialidade de argilas de queima clara como matérias-primas para o desenvolvimento de novos produtos cerâmicos - Sales Júnior, José Carlos Calado (2008)
The industries of structural ceramics are among the most important production chains in the state of Rio Grande do Norte. The industry and other interest groups to target the replacement of firewood by natural gas. Studies accordingly concluded that simple change does not guarantee products of superior quality, and that the increase in spending on fuel can economically cripple the use of gas for burning the majority of products manufactured by that action. However some proposals of innovations in terms of process and product are being studied in an attempt to justify the use of natural gas in industry, structural ceramics. One of the aspects investigated is the development of ceramic products differentiated, with new designs and greater value added. Inserted in that context, this paper aims to investigate the potential use of clay-firing clear fabrication of the "bricks of apparent joins drought", a new ceramic product with an innovative way. The development of the work was done in three stages. In the initial stage was held the characterization of raw materials, sought information on physical, chemical, mineralogical and mechanical samples. In the second stage five bodies were made using two of the nine ceramic clay characterized the first step. The masses were analyzed and compared with respect to the size distribution, plasticity and technological properties. In the last part of this work was carried out tests on massive bricks manufactured on an industrial scale. The results show that the nine clays can be used in the manufacture of new ceramic products, is the only constituent of mass ceramic or by mixing with other(s) clay(s